ANALISIS KENYAMANAN TERMAL PADA RUANG TERBUKA HIJAU PUBLIK: STUDI KASUS TAMAN KOTA ALUN-ALUN DEMAK - Nila Siti Zaitun (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Alun-Alun Demak City Park is the primary public green open space in Demak Regency, characterized by high visitor intensity yet limited research on its thermal comfort conditions. This study aims to analyze the thermal comfort level of the area using an objective approach through the Temperature Humidity Index (THI) and a subjective approach through the Thermal Sensation Vote (TSV), along with spatial distribution mapping using GIS. Measurements were conducted over three consecutive days in August 2025 at 16 sampling points arranged in a 4×4 grid pattern, covering three time sessions: morning (07:00–09:00), midday (12:00–14:00), and afternoon (16:00–18:00). TSV data were collected from 96 respondents using the seven-point ASHRAE scale. Results indicate that all 16 sampling points were in the Comfortable category in the morning session (THI 23.5–24.3). During midday, 14 points fell into the Uncomfortable category while 2 points (T12 and T16) reached the Very Uncomfortable category (THI = 30.5). Based on daily averages, all points fell into the Uncomfortable category (THI 27.3–28.2). TSV analysis revealed that 74% of respondents perceived the thermal environment as slightly hot to very hot. Pearson correlation between THI and TSV yielded r = 0.71 (strong positive), indicating strong alignment between objective measurements and subjective perception. Wide-canopy shade trees demonstrably reduced temperature by 1–2°C compared to hardscape areas. The study recommends adding shade vegetation, replacing paving blocks with grass blocks, and incorporating water features in the southern and central zones as strategies to improve thermal comfort.